Hydrophobic Graphene Quantum Dots for Defect Passivation and Enhanced Moisture Stability of CH3NH3PbI3 Perovskite Solar Cells. Issue 7 (29th March 2022) - Khorshidi, Elahe; Rezaei, Behzad; Blätte, Dominic; Buyruk, Ali; Reus, Manuel A.; Hanisch, Jonas; Böller, Bernhard; Müller-Buschbaum, Peter; Ameri, Tayebeh
Abstract : Passivating the defects and grain boundaries (GBs) of perovskite films at the interface by interface engineering is a promising route to achieve efficient and stable perovskite solar cells (PSCs). Herein, a new type of graphene, that is, hydrophobic graphene quantum dots (HGQDs) containing amide linkages, which consist of carbonyl and dodecyl amine groups, is successfully used as a bifunctional interface modifier to engineer the interface of the perovskite/hole transport layer. A comprehensive characterization including X‐ray photoelectron spectroscopy, Fourier‐transform photocurrent spectroscopy, Raman spectroscopy, photoluminescence spectroscopy, and space‐charge‐limited current measurements is performed to identify the underlying passivation mechanisms. It can be demonstrated that the HGQDs, due to the bifunctional groups containing N and O atoms, effectively passivate the uncoordinated Pb 2+ ions at the perovskite film surface and GBs and consequently induce a lower trap state density. Moreover, HGQDs enhance the quality of the perovskite film which reduces the charge recombination at the interface. Therefore, the power conversion efficiency of PSCs treated with HGQDs is significantly increased from 16.00% to 18.30%, mainly based on the improved open‐circuit voltage and fill factor. Importantly, the HGQDs featuring hydrophobicity due to alkyl chains significantly enhance moisture stability. Abstract : Hydrophobic graphene quantum dots (HGQDs) containing amide linkages, which consist of carbonyl and dodecyl amine groups, are successfully applied as an efficient bifunctional interface modifier to simultaneously boost the power conversion efficiency and stability of perovskite solar cells.